(untitled) (Journal of Computational Mathematics, 2001)
This paper is concerned with the numerical solution of delay differential equations (DDEs). We focus on the error behaviour of Runge-Kutta methods for stiff DDEs. We investigate D-convergence properties of algebraically stable Runge-Kutta methods with three kinds of interpolation procedures.